Investigation of articulating surfaces of single-pole endoprosthesis of the femoral head - Samoilenko, Olexsandr; Lukyanchenko, Volodimir; Dubonosov, Volodimir; Krut, Andrey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Unipolar hip replacement after femoral neck fracture in elderly patients enables them to move independently as soon as possible but complications in the late period stipulate to the search for new design solutions. Objective: To investigate the qualitative and chemical characteristics of the heads of single-pole hip joint endoprostheses made of titanium and stainless steel. Methods: The medical records of patients with late complications after unipolar hip replacement were studied. Using a microscope and spectrometer ElvaX MSB-2 we investigated 12 endoprosthesis removed after complications, fragments of bone cement and bone tissue from the area of inflammation. Results: Decreasing of the part of iron on 1 %, molybdenum on 8.3 % in local wear of the upper pole of the implant head made of stainless steel was revealed but the amount of nickel, chromium and manganese remained unchanged. In the case of surface defect there was decreasing of the part of chromium on 24.6 %, molybdenum on 20.8 %, and manganese on 80 %. In bone tissue adjacent to the neck of the implant chrome chromium (1.1 %) and iron (0.8 %) were detected. In the regions of wear on the surface of titanium heads there was detected decreasing in the proportion of titanium on 1.4 % increasing in the ratio of calcium and potassium on 3.3 times, and the ratio of molybdenum, vanadium, iron, scandium remained unchanged. In bone tissue nearby the neck of the implant titanium was discovered up to 0.8 %. Conclusion: the biological environment of the human body on the surface of the endoprosthesis made of titanium and stainless steel active chemical processes occur. Protective bioinert coating of the head of the unipolar endoprosthesis should extend its work and to improve the tribological properties its surface.